Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1161/01.cir.74.4.684
|View full text |Cite
|
Sign up to set email alerts
|

Time variation of mitral regurgitant flow in patients with dilated cardiomyopathy.

Abstract: Angiographic results in patients with mitral regurgitation suggest that up to 50% of the regurgitant volume occurs during the preejection period. This contrasts markedly with the electromagnetic measurements of mitral regurgitant flow in anesthetized dogs, which suggest that only 5% of mitral regurgitant flow occurs during the preejection period. Therefore, we used two-dimensional and Doppler echocardiography to quantify mitral regurgitation during aortic ejection and in the preejection and postejection period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
(4 reference statements)
0
4
1
Order By: Relevance
“…Xiao et al 15 reported electromechanical delay to activate the LV in DCM patients with a wide QRS that was evaluated from the onset of the QRS to the onset of MR, negatively correlated to the PR duration and reduced when compared to controls with narrow QRS duration. Preload and afterload conditions, duration of LV filling, and the PR interval interfered with the time course of the MR, 16 and this electromechanical delay may not be comparable with the time for LV activation measured in the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Xiao et al 15 reported electromechanical delay to activate the LV in DCM patients with a wide QRS that was evaluated from the onset of the QRS to the onset of MR, negatively correlated to the PR duration and reduced when compared to controls with narrow QRS duration. Preload and afterload conditions, duration of LV filling, and the PR interval interfered with the time course of the MR, 16 and this electromechanical delay may not be comparable with the time for LV activation measured in the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…1 In normal condition, the stroke volume gradually increases during exercise, 2,3 whereas in HF patients, exercise-induced changes in forward stroke volume have been shown to be inversely related to the extent of dynamic mitral regurgitation (MR). [4][5][6] Functional MR, a frequent condition in HF, is characteristically dynamic with intermittent changes in regurgitant volume in relation with loading conditions, [5][6][7][8][9] changes in LV shape, and dynamic LV dyssynchrony. 9,10 An exercise increase by !13 mm 2 in mitral effective regurgitant orifice is associated with a three-fold greater risk of cardiac-related death.…”
Section: Introductionmentioning
confidence: 99%
“…Regurgitation of left-sided cardiac valves is more commonly associated with structural abnormalities of either the valves or the supporting structures [1][2][3][4][5]. The development of regurgitation of all 4 cardiac valves, then, would appear to require abnormalities of the left sided cardiac valves and pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients had severely dilated left ventricles with a mean left ventricular end-diastolic dimension of 7.4 ± 0.8 cm (p < 0.01), without evidence of calcification of mitral or aortic valves. The third group consisted of 2 young patients with rheumatic heart disease, 1 with severe mitral stenosis, and the other with rheumatic aortic and mitral insufficiency.The detection of valvular regurgitation has become one of the major clinical applications of Doppler echo cardiography [1][2][3][4][5][6][7][8][9][10][11]. In recent years, it has become obvious that some of the regurgitation that is detected is of academic interest only, with little clinical significance [12][13][14], Regurgitation in the absence of cardiac pathol ogy is most commonly seen in the tricuspid and pul monic valves [7][8][9][10][11], We undertook this study to exam ine the frequency of Doppler-detected regurgitation of all 4 cardiac valves in a hospital-based echocardiography laboratory, and to determine what underlying échocar diographie features are seen with regurgitation of all 4 cardiac valves.…”
mentioning
confidence: 99%